2019
DOI: 10.1186/s12879-019-3989-0
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitosis in relation to CD4 count and anemia among ART initiated patients in St. Mary Aksum general hospital, Tigray, Ethiopia

Abstract: Background The geographical distribution of intestinal parasites with conditions of poverty in most countries of sub-Saharan Africa coincides with that of HIV/AIDS. However, there is paucity of studies investigating the relationship between intestinal parasitic infections with CD4 counts and anemia in HIV/AIDS patients starting Antiretroviral Therapy (ART) in this region particularly and in Ethiopia in general. The aim of this study was to determine the prevalence of intestinal parasitic infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
(31 reference statements)
6
9
2
2
Order By: Relevance
“…The overall prevalence of intestinal parasites among HIV/AIDS patients in this study was found to be 25.3% which is comparable with reports from Axum 26.4%, 17 Gondar, Ethiopia 24.3%, 18 Mozambique 26.5% 19 and Brazil 24%. 20 However, it was found to be higher than ndings reported from Kombolcha, Dessie, Gondar and Kobo regions of Ethiopia, and Benin and Makurdi regions of Nigeria 13.9%, 17.6%, 20%, 16%, 18%, 20.9% respectively.…”
Section: Prevalence Of Intestinal Parasitessupporting
confidence: 87%
“…The overall prevalence of intestinal parasites among HIV/AIDS patients in this study was found to be 25.3% which is comparable with reports from Axum 26.4%, 17 Gondar, Ethiopia 24.3%, 18 Mozambique 26.5% 19 and Brazil 24%. 20 However, it was found to be higher than ndings reported from Kombolcha, Dessie, Gondar and Kobo regions of Ethiopia, and Benin and Makurdi regions of Nigeria 13.9%, 17.6%, 20%, 16%, 18%, 20.9% respectively.…”
Section: Prevalence Of Intestinal Parasitessupporting
confidence: 87%
“…Furthermore, the absence of publication bias was evidenced using Egger's test statistics with a p-value of 0.064. Finally, the association between diarrhea and intestinal parasitic infections among HIV/ AIDS patients within the included three studies has been examined and computed [16,19,32]. The pooled results of this study showed that HIV/AIDS patients who had a history of diarrhea were statistically significant as compared to their counterparts (AOR: 4.79 (95%CI: 1.53, 14.99)) ( Fig 6).…”
Section: Plos Onementioning
confidence: 93%
“…In this study, 22 cross-sectional articles were reported from one city administration and six regions of Ethiopia. Eight studies conducted in Amhara regional state [4,17,18,[30][31][32][33][34], six studies were done in Oromia regional state [28,[35][36][37][38][39], four studies conducted in South Nations, Nationalities and Peoples Regional state (SNNPR) [5,29,40,41], two articles reported from Tigray regional state [16,21], one study reported from Harari regional state [19] and one study was conducted in Oromia region, Afar region and Dire Dawa city administration [42] (Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the included studies were cross-sectional in their design. Eight (29.6%) of the studies included in this review were from the Oromia region [21][22][23][24][25][26][27], seven (25.9%) were from the Amhara regional state [6,9,[28][29][30][31][32], seven (25.9%) were from Southern Nations Nationalities and People's (SNNPs) regional state [33][34][35][36][37][38][39], Two(7.4%) studies were from Tigray regional state [26,40] and the remaining three (11.1%) were from Addis Ababa [41], Harar [42]and whole Ethiopia [43]. Reported burden of intestinal parasitosis ranged from 13.9% in Oromia [27]to 80.3% in Amhara regional state [9].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%